Analysis Figurative Language “Let Me Not To The Marriage Of True Minds” By William Shakespeare’s - Ristin Dwi Herlinawati; Fairuz Mufidah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Literary works are creations written with the aim of conveying an aesthetic impression. Literary works can take the form of prose, poetry, or drama. To make poetry more beautiful and easier to understand, a writer needs to understand the rules for creating good poetry. This research aims to analyze the various types of figurative language found in William Shakespeare's poem titled "Let Me Not to the Marriage of True Minds." The research focuses on the analysis of figurative language used in the poem. The objective is to identify the types of figurative language and understand their functions within the poem. The results of this study reveal that there are three types of figurative language found in the poem: metaphor, personification, and hyperbole.